Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 4 - Quadratic Functions - 4.5 Solving Equations by Factoring - 4.5 Exercises: 21

Answer

$\color{blue}{\left\{-6, 6\right\}}$

Work Step by Step

RECALL: $a^2-b^2=(a-b)(a+b)$ Since $36=6^2$, the given equation can be written as: $x^2-6^2=0$ Factor the binomial using the formula above to obtain: $(x-6)(x+6)=0$ Use the Zero-Factor Property by equating each factor to zero to obtain: $x-6=0$ or $x+6=0$ Solve each equation to obtain: $x-6=0 \\x=0+6 \\x=6$ or $x+6=0 \\x=0-6 \\x=-6$ Therefore, the solution set is $\color{blue}{\left\{-6, 6\right\}}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.